Antibacterial activity of Dillenia suffruticosa leaf extract against Xanthomonas oryzae pv. oryzae - Sani, Mohd Fardzryn (2016)
Bacterial leaf blight caused by seed-borne bacteria Xanthomonas oryzae pv. oryzae (Xoo) is an important rice disease which caused yield losses of up to 50% of actual yield. Recently, chemical control method used to suppress the disease, but it causes harmful impact to human and environment. Natural plant extract offers safe and eco-friendly way to control plant disease. Dillenia suffruticosa has been reported as a medicine for various diseases but, the use of D. suffruticosa extracts to control the growth of any plant pathogen has not been reported. The objective of this study was to determine the antibacterial effect of D. suffruticosa leaf extracts against Xoo in vitro. Agar-well diffusion method was used to screen the antibacterial activity of D. suffruticosa leaf extracts against Xoo. Methanol, ethanol and water leaf extracts with different concentrations (0, 25, 50, 100 and 200 mg/mL) were tested. Methanol and ethanol leaf extracts possess significant inhibitor effect against Xoo with the inhibition zones ranges from 16.03-21.55 mm and 12.65-18.98 mm, respectively. The minimum inhibitory concentration and minimum bactericidal concentration of the methanol extract was 1.56 mg/mL and 6.25 mg/mL, respectively, obtained with macro-broth dilution technique. The Gas chromatography–Mass spectrum analysis identified the presence of sixteen bioactive compounds in the extracts; 2-Propanone, 1-hydroxy-, Propanoic acid, 2-Propenoic acid, 2-Propanone, 1,1-dichloro-, 2-Pentanone, 4-hydroxy-4-methyl-, 1,3-Butadiene-1-carboxylic acid, 1,1,2-Triacetoxyethane, Tridecane, 2,5-dimethyl-, Neophytadiene, 7-Octadecyne, 2-methyl-, Trichloroacetic acid, undec-2-enyl ester, n-Hexadecanoic acid, 2- Phytol, 9,12-Octadecadienoyl chloride, (Z, Z)-, Octadecanoic, acid and Vitamin E. The results of this study inferred that extract from D. suffruticosa leaf can provide an alternative for antibacterial option.